Optimizing autologous nonmobilized mononuclear cell collections for cellular therapy in pediatric patients with high‐risk leukemia. Issue 6 (25th April 2017) - Even‐Or, Ehud; Di Mola, Maria; Ali, Muhammad; Courtney, Sarah; McDougall, Elizabeth; Alexander, Sarah; Schechter, Tal; Whitlock, James A.; Licht, Christoph; Krueger, Joerg
Abstract : BACKGROUND: The manufacturing of cellular products for immunotherapy, such as chimeric antigen receptor T cells, requires successful collection of mononuclear cells. Collections from children with high‐risk leukemia present a challenge, especially because the established COBE Spectra apheresis device is being replaced by the novel Spectra Optia device (Optia) in many institutions. Published experience for mononuclear cell collections in children with Optia is lacking. Our aim was to compare the two collection devices and describe modified settings on the Optia to optimize mononuclear cell collections. STUDY DESIGN AND METHODS: As a quality initiative, we retrospectively collected and compared data from mononuclear cell collections on both devices. Collected data included patient's clinical characteristics; collection parameters, including precollection lymphocyte/CD3 counts, total blood volumes processed, runtimes, and side effects (including complete blood count and electrolyte changes); and product characteristics, including volumes and cell counts. Collection efficiencies and collection ratios were calculated. RESULTS: Twenty‐six mononuclear cell collections were performed on 20 pediatric patients: 11 with COBE and 15 with Optia. Adequate mononuclear cell products were successfully collected with a single procedure from all patients except one, with mean calculated mononuclear cell collection efficiency that was significantly higher from Optia collections compared with COBE collections (57.9 ± 4.6% vs 40.3 ± 6.2%, respectively; p = 0.04). CD3‐positive yields were comparable on both machines (p = 0.34) with significantly smaller blood volumes processed on Optia. Collected products had larger volumes on Optia. No significant side effects attributed to the procedure were noted. CONCLUSION: M ononuclear cell apheresis using the Optia device in children is more efficient and is as safe as that with the COBE device.